Development Strategy for Village-Owned Enterprises in the VUCA Era - Sufridayani, Kadek; Oka Martini, Ida Ayu (International Journal of Social Science and Business, 2024)
This research explores the development strategies of Village-Owned Enterprises (BUMDes) in Kabupaten Buleleng in the face of the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era. The rapid advancement of digital technology has brought significant changes to various industrial sectors, including BUMDes. The main aim of this study is to identify development strategies for BUMDes in the VUCA era using a phenomenological approach. Data was collected through in-depth interviews with the Department of Community and Village Empowerment (Dinas PMD), village officials, and BUMDes managers, as well as participatory observation and document analysis. The SWOT analysis revealed the internal strengths and weaknesses of BUMDes, as well as external opportunities and threats. Based on this analysis, several strategies are proposed:  1) SO Strategy: Maximizing BUMDes' strengths, such as technological facilitation, positive relationships with the government, and innovative products to develop technology-focused business units. 2) ST Strategy: Utilizing strengths like competitive products and well-trained human resources to overcome threats from other BUMDes. Competing on pricing and building harmonious relationships with the government and the community. 3) WO Strategy: Addressing internal weaknesses, such as the quality of human resources, by leveraging opportunities. Providing training to enhance the quality of human resources and implementing Community Social Responsibility (CSR) programs that involve the creativity of the community to support BUMDes activities. 4) WT Strategy: Minimizing weaknesses and avoiding threats. Training human resources in technology and financial management, and addressing the limited internet access through coordination with the government.